The relationship between access and quality of urban green space with population physical activity. - Hillsdon, M; Panter, J; Foster, C; Jones, A (2006)
OBJECTIVES: This study examined the association between access to quality urban green space and levels of physical activity. STUDY DESIGN: A cross-sectional examination of the relationship between access to quality urban green space and level of recreational physical activity in 4950 middle-aged (40-70 years) respondents from the European Prospective Investigation into Cancer and Nutrition (EPIC), who resided in Norwich, UK. METHODS: Using geographic information systems (GIS), three measures of access to open green space were calculated based on distance only, distance and size of green space and distance, size and quality of green space. Multiple regression models were used to determine the relationship between the three indicators of access to open green space and level of recreational physical activity. RESULTS: There was no evidence of clear relationships between recreational activity and access to green spaces. Non-significant associations were apparent for all variables, and there was no evidence of a clear trend in regression coefficients across quartiles of access for either the distance, size adjusted, and quality and size-adjusted models. Furthermore, the neighbourhood measures of access to green spaces showed non-significant associations with recreational physical activity. CONCLUSIONS: Access to urban green spaces does not appear to be associated with population levels of recreational physical activity in our sample of middle-aged adults.